DYSPHAGIA AFTER CERVICAL SPINE SURGERY: A REPORT OF TWO CASES - TORIYAMA, Y.; KOSAKI, K.; KOSAKI, H. (Stomato-pharyngology, 1990)
Two patients with dysphagia after anterior compression and fusion of the cervical spine are reported. Case 1, a 40-years-old man, with ankylosing spondilitis and anterior decompression and fusion of the third and fourth cervical vertebrae. He complained of dysphagia after the operation. Case 2, a 56-years-old man, complained of hoarseness and dysphagia had been dignosed Forestier's disease first. Later he developed quadriplegia. Anterior decompression and fusion of the fourth, fifth, and sixth cervical vertebrae were performed under the diagnosis of diffuse idiopathic skeletal hyperostosis (DISH). After the operation, dysphagia developed. In Japan, About 30 cases of Forestier's disease with dysphagia had been reported and some were treated by removal of osteophytes. Today, Forestier's disease is considered to be a subtype of diffuse idiopathic skeletal hyperostosis (DISH) For anterior decompression and fusion of the cervical spine, there are two major approaches: Whitedides-Kelly approach and Smith-Robinson approach. The latter is the most common used. Osteophytes are removed during this operation, but as we pass through the retropharyngeal space and change the shape of the cervical spine, dysphagia may bea result.